Prognostic Value of Normal Thyroid Stimulating Hormone in Long-Term Mortality in Patients With STEMI - Sun, Lijie; Xiao, Keling; Miao, Zupei; Zhang, Yinghua; Si, Jin; Shi, Ning; Zhang, Haoyu; Zhao, Ting; Li, Jing (Frontiers in Endocrinology, 2022)
Background: Although within the normal range, thyroid stimulating hormone (TSH) levels are associated with cardio-metabolic disorders and have an effect on cardiovascular system. The aims of our study was to assess prognostic value of normal TSH on long-term mortality in patients with ST-segment elevation myocardial infarction (STEMI). Methods: Consecutive STEMI patients who had TSH level within normal range (0.55-4.78 uIU/ml) were enrolled from November 2013 to December 2018. Patients were stratified into three groups depending on the tertile of TSH level and were compared all-cause mortality and cardiac death. TSH concentrations associated with risk of all-cause mortality were evaluated in a continuous scale (restricted cubic splines) and the Cox proportional hazards regression model. Results: A total of 1203 patients with STEMI were eligible for analysis. During a median follow up of 39 months, patients in the 3rd tertile group had higher all-cause mortality (20.1% vs. 12.2% and 14.3%, P=0.006) and cardiac death (15.4% vs. 7.7% and 12.3%, P=0.001) as compared to the 1st and 2nd tertile groups. The Cox proportional hazards model showed that TSH was an independently predictor on long-term all-cause mortality (HR:1.248, 95% CI:1.046-1.490, P=0.014). However, subgroup analysis indicated that TSH (HR:1.313, 95% CI: 1.063-1.623, P=0.012) were only significantly associated with long-term all-cause mortality in the patients without emergency reperfusion therapy. Restricted cubic spline analyses showed a linear relationship between TSH concentrations and all-cause mortality (P for non-linearity = 0.659). Conclusions: Higher TSH level - even in a normal range is associated with long-term mortality in patients with STEMI, proposing an additional indication to identify STEMI patients with poor prognosis.